A Distance and Pixel Intensity Relation for Disparity Mapping in Region of Interest - Hamzah, Rostam Affendi; Hamid, Mohd Saad; Rosly, Hasrul Nisyam (2011)
This paper presents an analysis of range and pixel intensity region of interest in selected area or segment of disparity mapping in application of stereo vision. The mapping is about to deal with the intensities of pixels which allocate the depths of an image and can be extracted to get the distance values. This region is a reference view of the stereo camera and stereo vision baseline is based on horizontal configuration.